Sistem Pendukung Keputusan Penentuan Kesesuaian Lahan Tanaman Andaliman Dengan Metode Profile Matching Di Kecamatan Merdeka Kabupaten Karo - Roma Sinta Simbolon; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2020)
Andaliman is a commodity plant which has many benefits and high selling power. Andaliman plants are difficult to cultivate because of the difficulty of determining the suitability of land suitable for these plants and the absence of researchers who have conducted research on these plants. Therefore, a decision support system is needed that can assist in determining the suitability of andaliman plantations by using three criteria consisting of each sub-criteria, namely Soil Classification (which consists of soil Ph sub-criteria, soil type and humidity), Land conditions. (which consists of sub-criteria for altitude and light intensity), and climate (which consists of sub-criteria for air temperature and rainfall). A decision support system is a system which able to provide both problem-solving abilities and communication skills for semi-structured problems. This research system aims to design a system in determining the suitability of land for andaliman plants using the Profile Matching method, which is one of the methods in the DSS that uses the GAP weighting method. The programming language used in making the system is PHP with MySQL database. The results of the implementation of the system that have been made show that Jaranguda Village is the most suitable village for planting Andaliman plants.